Translate e Publish Elfriede Jelinek’s Theatre in Brazil: Why, What and How? - Bohunovsky, Ruth (2021)
This article presents a translation project, currently underway,which aims to translate theatre texts from de Austrian author ElfriedeJelinek. It briefly addresses to the tradition of theatre translation in Brazil,the criteria for the selection of the texts to be translated, the theoreticalbias and the concept of collaborative translation. The reflections presentedhere deal with three guiding questions: why translate Elfriede Jelinek’stheatre in Brazil? Which works should be translated? How can they betranslated?